Cardiac cachexia and muscle wasting: definition, physiopathology, and clinical consequences - Okoshi, Marina Politi [UNESP]; Romeiro, Fernando Gomes [UNESP]; Martinez, Paula Felippe [UNESP]; Oliveira Junior, Silvio Assis de [UNESP]; Polegato, Bertha Furlan [UNESP]; Okoshi, Katashi [UNESP] (Taylor & Francis, 2014)
Cachexia and muscle wasting are frequently observed in heart failure patients. Cachexia is a predictor of reduced survival, independent of important parameters such as age, heart failure functional class, and functional capacity. Muscle and fat wasting can also predict adverse outcome during cardiac failure. Only more recently were these conditions defined in International Consensus. Considering that heart failure is an inflammatory disease, cardiac cachexia has been diagnosed by finding a body weight loss .5%, in the absence of other diseases and independent of other criteria. Muscle wasting has been defined as lean appendicular mass corrected for height squared of 2 standard deviations or more below the mean for healthy individuals between 20 years and 30 years old from the same ethnic group. The etiology of heart failure-associated cachexia and muscle wasting is multifactorial, and the underlying physiopathological mechanisms are not completely understood. The most important factors are reduced food intake, gastrointestinal alterations, immunological activation, neurohormonal abnormalities, and an imbalance between anabolic and catabolic processes. Cachexia and muscle wasting have clinical consequences in several organs and systems including the gastrointestinal and erythropoietic systems, and the heart, previously affected by the primary disease. We hope that a better understanding of the mechanisms involved in their physiopathology will allow the development of pharmacological and nonpharmacological therapies to effectively prevent and treat heart failure-induced cachexia and muscle wasting before significant body weight and muscle wasting occurs.
Keywords: Heart failure; Prognosis; Anorexia; Inflammatory activation; Cardiac wasting